2022
DOI: 10.3390/nano12152640
|View full text |Cite
|
Sign up to set email alerts
|

FeNi LDH/V2CTx/NF as Self-Supported Bifunctional Electrocatalyst for Highly Effective Overall Water Splitting

Abstract: The development of bifunctional electrocatalysts with efficient oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) is still a key challenge at the current stage. Herein, FeNi LDH/V2CTx/nickel foam (NF) self-supported bifunctional electrode was prepared via deposition of FeNi LDH on V2CTx/NF substrate by hydrothermal method. Strong interfacial interaction between V2CTx/NF and FeNi LDH effectively prevented the aggregation of FeNi LDH, thus exposing more catalytic active sites, which improved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…Lv et al [28] fabricated Co 2 P/N@Ti 3 C 2 T x @NF electrocatalysts with multi-heterostructure interfaces and porous structures, showing excellent HER activity and long-term durability. MXene (Ti 3 C 2 T x ), as a new class of two-dimensional (2D) materials, possess the advantages of good electrical conductivity, good surface hydrophilicity, and good chemical stability, making them ideal supporting materials for water splitting [29][30][31][32]. In addition, the construction of the MXene-based heterostructures facilitates the enrichment of the active sites and expands the contact between the electrolyte and the active sites, thereby enhancing the catalytic activity [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Lv et al [28] fabricated Co 2 P/N@Ti 3 C 2 T x @NF electrocatalysts with multi-heterostructure interfaces and porous structures, showing excellent HER activity and long-term durability. MXene (Ti 3 C 2 T x ), as a new class of two-dimensional (2D) materials, possess the advantages of good electrical conductivity, good surface hydrophilicity, and good chemical stability, making them ideal supporting materials for water splitting [29][30][31][32]. In addition, the construction of the MXene-based heterostructures facilitates the enrichment of the active sites and expands the contact between the electrolyte and the active sites, thereby enhancing the catalytic activity [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…In the Ni 2p region of the NiFe@LDH electrocatalysts spectra, two peaks at binding energies (BEs) of 856.59 and 874.38 eV were identified as Ni 2p 3/2 and Ni 2p 1/2 of Ni 2+ , respectively. Two additional peaks, identified as satellite peaks, were observed at 862.26 and 879.84 eV (Figure a) . In the Fe 2p XPS spectra, two dominant peaks at 712.7 and 725.9 eV were attributed to Fe 2p 3/2 and Fe 2p 1/2 , correspondingly, with two satellite peaks observed at 718.3 and 731.4 eV (Figure b).…”
Section: Resultsmentioning
confidence: 95%
“…Two additional peaks, identified as satellite peaks, were observed at 862.26 and 879.84 eV (Figure 3a). 28 In the Fe 2p XPS spectra, two dominant peaks at 712.7 and 725.9 eV were attributed to Fe 2p 3/2 and Fe 2p 1/2 , correspondingly, 29 with two satellite peaks observed at 718.3 and 731.4 eV (Figure 3b). These characteristics represent the presence of Ni and Fe in the oxidation states of Ni 2+ and Fe 3+ .…”
Section: Chemical Phase Analysismentioning
confidence: 98%
“…When compared with the prepared materials, NRPC/NiMn displays smaller Tafel slope of 78 mV dec −1 , comparable to the reported non-noble metal oxides [NCNT/Ni-NiFe 2 O 4 (76 mV dec −1 ) and NCNT/Ni-NiMn 2 O 4 (85 mV dec −1 )]. It is observed that the catalytic property of NRPC/NiMn is efficient towards OER and HER due to the following reasons: the hierarchical three-dimensional flower-like morphology of NRPC/NiMn can speed up the transport of electrons and ions through increased surface area; the anchoring of these metal oxides on carbon spheres avoids agglomeration of these particles, providing excellent structural stability of NRPC/NiMn; and the inclusion of hetero-atom-doped carbon (NRPC) and bimetallic compounds results in providing more active sites at the interface of the electrode and electrolyte due to variable oxidation and reduction states of the metals and synergistically improves the OER process [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%